2011
DOI: 10.1016/j.ejsobi.2011.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Plant species effects on soil macrofauna density in grassy arable fallows of different age

Abstract: The density of soil macrofauna groups in nine grassy arable fallows of different age were investigated in a factorial design with the factors ‘plant species’ (legume: Medicago sativa , herb: Taraxacum officinale , grass: Bromus sterilis ) and ‘age class’ (A1: 2–3/3–4, A2: 6–8/7–9, A3: 12–15/13–16 years in 2008/2009). Four plots were selected randomly at each fallow. In May 2008 and May 2009, within each plot five M. sativa … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
10
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 56 publications
3
10
0
Order By: Relevance
“…RDA results for belowground macro‐invertebrates indicated that the Myriapods ( S. morsitans ), Coleopterans (Pachlister caffer ), and Isopterans ( H. mossambicus ) benefited most from high concentration of limiting soil nutrients (N, P, K, and C) on abandoned kraals. Similar findings have been recorded on nutrient‐rich areas by others (Doblas‐Miranda et al., ; Riggins et al., ; Salamon et al., ; Wu, Zhang, & Wang, ). Soils rich in N, P, K, and C are associated with high microbial biomass (Lavelle, ) which could have directly or indirectly attracted these species.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…RDA results for belowground macro‐invertebrates indicated that the Myriapods ( S. morsitans ), Coleopterans (Pachlister caffer ), and Isopterans ( H. mossambicus ) benefited most from high concentration of limiting soil nutrients (N, P, K, and C) on abandoned kraals. Similar findings have been recorded on nutrient‐rich areas by others (Doblas‐Miranda et al., ; Riggins et al., ; Salamon et al., ; Wu, Zhang, & Wang, ). Soils rich in N, P, K, and C are associated with high microbial biomass (Lavelle, ) which could have directly or indirectly attracted these species.…”
Section: Discussionsupporting
confidence: 88%
“…Soils rich in N, P, K, and C are associated with high microbial biomass (Lavelle, ) which could have directly or indirectly attracted these species. Dung and carrion that is commonly found on abandoned kraals (Riginos et al., ) could have attracted a wide variety of coprophagous and necrophagous species, for instance the Coleopterans (Salamon et al., ). On the other hand, abandoned kraals enhance the microclimate for a variety of soil and litter dwellers through good nutrient supply for plant growth (Muchiru et al., ) and ultimately improved the quality and quantity of litter (Mathieu et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wissuwa et al (2013) and Zhu and Zhu (2015) found a significant positive correlation between soil organic matter content and Oribatida abundance. Bedano and Ruf (2007), Salamon et al (2011) as well as Wissuwa and Salamon (2012) reported a significant influence of soil organic matter on Gamasida density. The relationship between Gamasida and soil organic matter is indirect.…”
Section: Discussionmentioning
confidence: 99%
“…Diverse crop rotations, together with absence of herbicide, often increase biomass of soil organisms (bacteria, fungi and micro and macro invertebrates, Alteri 1999), which can support larger populations of surface-active invertebrates captured in pitfall traps (e.g. Salamon et al 2011). Use of manure in place of synthetic fertilizers will enhance this relationship (Alteri 1999), but I do not have data on long-term fertilizer use in my study fields.…”
mentioning
confidence: 99%